The Association Between Psychological Distress and Cancer Mortality in the United States: Results from the 1997-2014 NHIS-NDI Record Linkage Study - Lee, Hyunjung; Singh, Gopal K (Annals of behavioral medicine, 2021)
Psychological distress can influence cancer mortality through socioeconomic disadvantage, health-risk behaviors, or reduced access to care. These disadvantages can result in higher risks of cancer occurrence, a delayed cancer diagnosis, hamper adherence to treatment, and provoke inflammatory responses leading to cancer. Previous studies have linked psychological distress to cancer mortality. However, studies are lacking for the U.S. population. This study examines the Kessler six-item psychological distress scale as a risk factor for U.S. cancer mortality using the pooled 1997-2014 data from the National Health Interview Survey (NHIS) linked to National Death Index (NDI) (N = 513,012). Cox proportional hazards regression was used to model survival time as a function of psychological distress and sociodemographic and behavioral covariates. In Cox models with 18 years of mortality follow-up, the cancer mortality risk was 80% higher (hazard ratio [HR] = 1.80; 95% CI = 1.64, 1.97) controlling for age; 61% higher (HR = 1.61; 95% CI = 1.46, 1.76) in the SES-adjusted model, and 33% higher (HR = 1.33; 95% CI = 1.21, 1.46) in the fully-adjusted model among adults with serious psychological distress (SPD), compared with adults without psychological distress. Males, non-Hispanic Whites, and adults with incomes at or above 400% of the federal poverty level had greater cancer mortality risk associated with SPD. Using an 8 years of mortality follow-up, those with SPD had 108% increased adjusted risks of mortality from breast cancer. Our study findings underscore the significance of addressing psychological well-being in the population as a strategy for reducing cancer mortality.